1992
DOI: 10.1093/bja/68.6.580
|View full text |Cite
|
Sign up to set email alerts
|

Continuous Extradural Analgesia: Comparison of Midwife Top-Ups, Continuous Infusions and Patient Controlled Administration

Abstract: We have compared three techniques used to provide extradural analgesia during the first stage of labour: 0.25% plain bupivacaine 10 ml demand top-ups delivered by the midwife; continuous infusion of 0.125% plain bupivacaine 10 ml h-1; and patient-controlled extradural analgesia (PCEA) delivering 3-ml boluses of 0.25% bupivacaine. Each technique produced comparable analgesia achieving equivalent maternal satisfaction, with no difference in mode of delivery and no complications. This regimen for PCEA proved a vi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
29
1
1

Year Published

2000
2000
2009
2009

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 69 publications
(32 citation statements)
references
References 6 publications
1
29
1
1
Order By: Relevance
“…PCEA produced similar levels of pain relief in most studies in terms of recorded Visual Analogue Scores for pain (135,137,140,(145)(146)(147)(148)(149)(150)(151)(152)(153)(154)(155). However, quality of pain relief is more than recorded VAS scores.…”
Section: Patient Controlled Epidural Analgesia (Pcea) Versus Continuomentioning
confidence: 85%
See 3 more Smart Citations
“…PCEA produced similar levels of pain relief in most studies in terms of recorded Visual Analogue Scores for pain (135,137,140,(145)(146)(147)(148)(149)(150)(151)(152)(153)(154)(155). However, quality of pain relief is more than recorded VAS scores.…”
Section: Patient Controlled Epidural Analgesia (Pcea) Versus Continuomentioning
confidence: 85%
“…Most studies also showed that local anaesthetic consumption is reduced with ITU (133,134,136,137). Despite less anaesthetic consumption, obstetric outcome is usually similar between the two modalities (135)(136)(137)(138)(139)(140), except for more spontaneous deliveries with ITU in the study by Smedstad et al (134). So basically, CEI and ITU are quite similar in terms of quality of analgesia and incidence of side-effects with a tendency towards better performance for the ITU technique.…”
Section: Intermittent Top-ups Versus Continuous Infusionmentioning
confidence: 96%
See 2 more Smart Citations
“…30,31 This technological advance significantly increases the satisfaction of labouring women particularly due to the sense of control while receiving epidural analgesia solutions. 32,33 The use of ropivacaine combined with the PCEA technique, at the University of Saskatchewan, provides the majority of labouring women the option to freely ambulate unassisted while receiving epidural analgesia. These changes now empower labouring women during one of life's most painful experiences with a sense of control and composure while retaining the physical strength and sensation necessary for childbirth.…”
mentioning
confidence: 99%